ASSESSMENT OF FUNCTIONAL AND CLINICAL OUTCOME OF ANTERIOR CRUCIATE LIGAMENT RECONSTRUCTION USING IPSILATERAL AUTOLOGOUS HAMSTRING GRAFT- A PROSPECTIVE STUDY. - Nilesh Kumar Agrawal; Kumar Rahul; Raman Kumar; Santosh Kumar (Student's Journal of Health Research Africa, 2024)
Background Anterior Cruciate Ligament Reconstruction using Autologous Ipsilateral Hamstring Graft is one of the commonest procedures performed for restoration of Knee Stability. The ACL is the main support of the knee joint and averts it against anterior movement. It also helps in preventing rotatory and valgus pressure. The chief goal of the present research is to investigate the functionality of ACL remodeling with conventional hamstring autograft. Materials and Methods This is prospective research that includes 40 subjects which was carried out in IGIMS, Patna, Bihar, India. The study was conducted for 1 year. The patients were utilizing the endo button and absorbable intervention screw to limit movement, post-surgery knee strength, and internal knee performance. Tegner Lysholm's knee scoring system was utilized for the evaluation of functioning results. Result The majority of the harm was caused by sports. The patients were followed up for 2 years after the surgery. Lysholm's score was upgraded postoperatively. All in all, fine outcomes followed after six months. The majority of the patients went back to their routine activity. 20 patients' injuries occurred on the right side and for the other 20 patients, injuries were on the left side. 24 patients had initial symptoms of lack of stability in the knee. 12 patients had pain and 4 patients suffered from locking. Conclusion In this research, it was deduced that arthroscopy-aided anterior cruciate ligament remodeling utilizing hamstring autograft gives stability to the knee, decreases post-surgery injuries, and provides speedy recovery. The outcomes regarding functionality are great, the patient activity becomes normal after some time and the patient can use the staircase easily. Recommendation Standard hamstring autograft is a great choice in the remodeling of the anterior cruciate ligament.